Targeting ATF5, CEBPB, and CEBPD with Cell-Penetrating Dpep Sensitizes Tumor Cells to NK-92MI Cell Cytotoxicity - Qing Zhou; Markus D. Siegelin; Lloyd A. Greene (Cells)
Natural killer (NK) cells are an important innate defense against malignancies, and exogenous sources of NK cells have been developed as anti-cancer agents. Nevertheless, the apparent limitations of NK cells in clearing cancers have suggested that their efficacy might be augmented by combination with other treatments. We have developed cell-penetrating peptides that target the transcription factors ATF5, CEBPB, and CEBPD and that promote apoptotic cancer cell death both in vitro and in vivo without apparent toxicity to non-transformed cells. We report here that one such peptide, Dpep, significantly sensitizes a variety of tumor cell types to the cytotoxic activity of the NK cell line, NK-92MI. Such sensitization requires pre-exposure of tumor cells to Dpep and does not appear due to effects of Dpep on NK cells themselves. Our findings suggest that Dpep acts in this context to lower the apoptotic threshold of tumor cells to NK cell toxicity. Additionally, while Dpep pre-treatment does not prevent tumor cells from causing NK cell “inactivation”, it sensitizes cancer cells to repeated rounds of exposure to fresh NK cells. These findings thus indicate that Dpep pre-treatment is an effective strategy to sensitize cancer cells to the cytotoxic actions of NK cells.